SWOT - AHP model for prioritization of strategies of the resort Stara Planina - Nikolic, Djordje; Spasic, Jelena; Zivkovic, Zivan; Djordjevic, Predrag; Mihajlovic, Ivan; Kangas, Jyrki (Serbian Journal of Management, 2015)
This paper presents the results of integrated SWOT analysis and Multi-criteria Decision Analysis (MCDA) model, employed for defining the development of resort Stara planina in Eastern Serbia and which was based on final report of previous expert study for this touristic destination. In accordance to defined SWOT factors and sub-factors six resulting strategies were generated as: SO strategies (based on the sub-factors of strengths and opportunities), WO strategy (based on the sub-factors of weaknesses and opportunities), ST strategies (based on the sub-factors of strengths and threats), and WT strategy (based on the sub-factors of weaknesses and threats). Relative importance weights of the SWOT factors and sub-factors were obtained by Analytic Hierarchy Process (AHP) model, as well as the ranking of identified strategies was performed by several experts. The results indicate that following sequence of strategies: SO1 → SO2 → ST1 → ST2 → WO1 → WT1, should be realized to complete the main goals for strategic development of the touristic destination Stara planina.